The interest of the Padang community towards halal products - Sunarsih Sunarsih (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
The emphasis on the importance of halal products is now growing. This quickly became a new market power and brand identifier and now moved to the main market, influencing and changing perceptions of how business should be done, including from a marketing standpoint. The purpose of this paper is to examine the application of reasoned action theory (TRA) in predicting interest in halal products among the Padang community. By using multiple regression analysis tools, there is evidence that subjective attitudes and norms have a positive and significant effect on public interest in halal products in the Padang community.